Transition from compression to strike-slip tectonic styles along the northern margin of the Levant Basin - (:unkn) unknown (My University, 2018)
The Cyprus Arc system is major plate boundary of the Eastern Mediterranean where different plates interact, namely Arabia, Africa, Eurasia, as well as the Anatolian micro-plate. It constitutes the northern boundary of the Levant Basin (of thin stretched continental crust) and the Herodotus Basin (of oceanic crust). The Cyprus Arc is directly linked with the northward convergence of the African continental plate with respect to the Eurasian continental plate since Late Cretaceous time. The indentation of the Arabian plate and the slab pull effect of the African plate roll back in the Aegean region on the eastern and western part of the Anatolian plate respectively, leads to the westward escape of Anatolia from Late Miocene to Recent, which results in a strike-slip component along the Cyprus Arc system and onshore Cyprus. Several scientific questions with regard to the geological setting of the region were investigated during this project. How is the deformation accommodated at the Cyprus Arc system? Is this deformation style affected by the variation of the crustal nature at each domain? How is this deformation recorded on the sedimentary pile onshore Cyprus? How does the onshore and offshore deformation connect within the geodynamic context of the region? In order to answer these scientific questions, 2D reflection seismic data were utilized, that image the main plate structures and their lateral evolution south and east of Cyprus. Interpretation of these data lead to the identification of nine tectono-sedimentary packages in three different crustal domains south of the Cyprus Arc system: (1) The Levant Basin (attenuated continental crust), (2) The Eratosthenes micro-continent (continental crust) and (3) The Herodotus Basin (oceanic crust). Within these domains, numerous tectonic structures were documented and analysed in order to understand the mechanism and timing of deformation. At the northern boundary of the Levant Basin domain, thrust faults ver
Keywords: African Research